Fuzzy data envelopment analysis for measuring agility performance of supply chains. (7th April 2011) - Abtahi, Amir-Reza; Khalili-Damghani, Kaveh
A conceptual model including capabilities and enablers of agility has been proposed for agility levels in agile supply chain (ASC). Then, a fuzzy data envelopment analysis (FDEA) has been proposed to measure the efficiency of transformation process in which a supply chain transforms enablers of agility into capabilities of agility. Proposed FDEA resulted in interesting reduction of computational efforts. Finally, a Monte Carlo simulation process has been supplied to rank the interval efficiency scores. Controlled simulated illustrative instance has been designed to address the ability of proposed procedure as a robust and straightforward tool.